2007
DOI: 10.1002/jcb.21410
|View full text |Cite
|
Sign up to set email alerts
|

Sperm nucleosomes disassembly is a requirement for histones proteolysis during male pronucleus formation

Abstract: We had previously reported that a cysteine-protease catalyzes the sperm histones (SpH) degradation associated to male chromatin remodeling in sea urchins. We found that this protease selectively degraded the SpH leaving maternal cleavage stage (CS) histone variants unaffected, therefore we named it SpH-protease. It is yet unknown if the SpH-protease catalyzes the SpH degradation while these histones are organized as nucleosomes or if alternatively these histones should be released from DNA before their proteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Previous pharmacological experiments demonstrated that a cathepsin L inhibitor I-sensitive protease remains necessary beyond the first cell cycle post-fertilization suggesting that this protease activity can play a role in regulation of chromatin structure along embryogenesis [6]. In agreement, northern blot and semi-quantitative PCR analyses demonstrated that the transcripts encoded by the identified cathepsin L gene are constantly expressed during sea urchin development.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Previous pharmacological experiments demonstrated that a cathepsin L inhibitor I-sensitive protease remains necessary beyond the first cell cycle post-fertilization suggesting that this protease activity can play a role in regulation of chromatin structure along embryogenesis [6]. In agreement, northern blot and semi-quantitative PCR analyses demonstrated that the transcripts encoded by the identified cathepsin L gene are constantly expressed during sea urchin development.…”
Section: Discussionsupporting
confidence: 59%
“…This substrate selectivity is also regulated by post-translational modification of the substrates: poly(ADP-ribosylation) of CS histones and phosphorylation of sperm specific histones [33], [34]. During this dramatic sperm chromatin remodelling it has been shown that previous disassembly of nucleosomes is required for complete histone proteolysis however the activity in charge of this displacement remains unidentified [6]. While in that case deposition of maternal histones on sperm DNA is replication independent, it has been suggested that H3 replacement in ESC is S-phase/replication coupled [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A candidate for the maternal kinase is Cdk2, because it colocalizes with the male pronucleus after fertilization (Schnackenberg and Marzluff, 2002;reviewed in Imschenetzky et al, 2003). Once their attachment has been loosened, sperm-specific histones are removed from sperm chromatin by a maternal sperm-nucleosome disassembly activity (SDNA) and then degraded by a maternal protease (Imschenetzky et al, 1997;Iribarren et al, 2008).…”
Section: Conversion Of the Sperm Nucleus Into A Male Pronucleusmentioning
confidence: 99%